Footwork and grip strength: Is it related to smash accuracy - Jeki Haryanto; Zulfikal Zulfikal; Donie Donie; Eval Edmizal (Global Econedu, 2021)
The accuracy of the badminton specialization students' smash is still far from what is expected, this is evident from where students when doing a smash just insert the shuttlecock into the opponent's area so they don't pay attention to the accuracy of the smash done. The weakness of the students is that they are not aware of the footwork function. This research is a type of correlational research that aims to determine the degree of relationship between footwork and grip strength with smash accuracy in badminton. The population of this study were students of specialization badminton courses. The sample in this study were students specializing in badminton, totaling 35 people with a total sampling technique. Data was collected by measuring the footwork through a footwork ability test, and grip strength was measured using the hand grip dynamometer. While the smash ability is measured through the smash test. Data analysis and hypothesis testing 1 and 2 used a simple correlation analysis technique, while hypothesis 3 used a multiple correlation analysis technique with a significant level= 0.05. From the data analysis, the following results were obtained: 1)Footwork has a significant relationship with the ability to smash in badminton, 2) Grip strength has a significant relationship with smash ability in badminton, 3) Footwork and grip strength together have a relationship with the accuracy of smash in the badminton game.